A magyar és a kelet-közép-európai kis- és középvállalkozások gazdasági teljesítményének és hatékonyságának vizsgálata : 2003-2008 - Stárics, Roland (Közép-Európai Közlemények, 2011)
The states of the region joined the European Union in two groups (eight countries in 2004 and two in 2007). In my opinion it is current to prepare a list of the changes occurred after the accession of the sector of the small and medium-sized enterprises (SMEs) of ten states in the region. Of which countries’ SME-sector did manage to approach the EU-average in the field of added value and productivity? Which countries failed to cut down on significantly their lag and what can be the reason for it? What kind of importance did the small and medium-sized enterprises have in certain countries before the EU-accession and do they have in 2008 in the field of added value and employment? The preparation of a comparative analysis is also justified by the fact that the international financial and economic crisis reached the countries of Eastern and Central Europe in the autumn of 2008 has drawn the attention to the local economies, including the small and medium-sized enterprises.